Strategi Komunikasi Pemasaran Sebagai Media Promosi Dalam Meningkatkan Penjualan Pada PT Tunas Jaya : Marketing Communication Strategy as a Promotional Media in Increasing Sales at PT Tunas Jaya ​ - Amelia, Shy She; Iswadi (Technomedia Journal, 2024)
The purpose of this research is to determine the function of marketing communication strategies as promotional media in increasing sales at PT Tunas Jaya. The method used in this research is a qualitative research method with the type of research used being a case study. The data collection methods used were interviews and observation. Based on the results of the research conducted, it is known that PT Tunas Jaya's marketing strategy in increasing sales is to use promotional media both offline and online. These two methods complement each other, and combine their respective functions to the maximum. The function of using offline promotional media from PT Tunas Jaya is to support increasing cooperation with state-owned and private companies. Meanwhile, using online promotional media, PT Tunas Jaya uses websites and social media, and directs its function to build public brand awareness of PT Tunas Jaya as well as the products it offers. These two promotional media have different marketing communication roles, but their goals are the same. Namely, to reach a wider audience, and maintain interaction with PT Tunas Jaya customers, both customers who have been familiar with the brand from the start, or new customers.